2013
DOI: 10.3762/bjoc.9.258
|View full text |Cite
|
Sign up to set email alerts
|

Flexible synthesis of anthracycline aglycone mimics via domino carbopalladation reactions

Abstract: A synthesis of anthracycline aglycone derivatives is described. The key step utilizes a powerful domino carbopalladation approach and subsequent ring closure. During this process two of the four rings of the anthracycline scaffold are formed. Differently substituted carbohydrates and dialkyne chains serve as versatile and simple starting materials for the reaction sequence. Diverse building blocks lead to a variety of different products and a broad range of structural diversity. 2194

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 49 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Miscellaneous other approaches for the synthesis of 1,2‐annulated carbohydrates, mainly involving transition‐metal‐catalyzed reactions, have been developed during the last years. Thus, based on their chroman syntheses,49 Leibeling and Werz described an interesting intramolecular domino carbopalladation of glycal‐derived bisalkynes (Scheme ) 50. The two units were linked by a silyl ether unit to give 100 , and palladium‐catalyzed cyclization proceeded smoothly to afford tetracycle 101 in 88 % yield.…”
Section: 12‐annulated Carbohydratesmentioning
confidence: 99%
“…Miscellaneous other approaches for the synthesis of 1,2‐annulated carbohydrates, mainly involving transition‐metal‐catalyzed reactions, have been developed during the last years. Thus, based on their chroman syntheses,49 Leibeling and Werz described an interesting intramolecular domino carbopalladation of glycal‐derived bisalkynes (Scheme ) 50. The two units were linked by a silyl ether unit to give 100 , and palladium‐catalyzed cyclization proceeded smoothly to afford tetracycle 101 in 88 % yield.…”
Section: 12‐annulated Carbohydratesmentioning
confidence: 99%
“…It should be noted that Pd­(OAc) 2 -catalyzed decarboxylative Heck cross-coupling of glucal 143 with 2,6-dimethoxybenzoic acid 280 under the assistance of Ag 2 CO 3 and PPh 3 in a mixture of dimethyl sulfoxide (DMSO) and DMF at 80 °C gave 2-deoxy-α- C -aryl glycoside 281 in 79% yield, whereas PdCl 2 -catalyzed desulfitative Ferrier-type C -glycosylation of glucal 143 with sodium p -chlorobenzenesulfinate 282 in the presence of CuCl 2 and LiCl in acetonitrile at 75 °C produced α- C -aryl glycoside 283 in 74% yield (Scheme ). , Moreover, Pd-catalyzed coupling of glycals with other classes of coupling partners such as trimethylsilyl cyanide, diethyl malonate, and silylated acetylide, also provided C -glycosides. …”
Section: C-glycosylation With Glycalsmentioning
confidence: 99%
“…Later on, the sugar-fused furan derivative 167 was synthesized by using 2-alkynyl- d -glucal derivatives 166 under AuCl 3 -catalyzed cyclization. Werz and his group 92 similarly utilized the Sonogashira–Hagihra cross-coupling reactions by using 2-bromogalactals 168 and observed that the 2-bromogalactals were less reactive as compared to the 1-iodoglycals. The authors assumed that the electron density at the C -2 position of glycals is high and that the 2-palladated glycal is a weak electrophile for electronically poor or neutral alkynes.…”
Section: Pd-catalyzed 2 C -Branched Sugar Synthesismentioning
confidence: 99%